POLEMIK PEMAKNAAN KASIDAH BURDAH AL-BUSIRY: KAJIAN ESTETIKA NEGATIF - Fadlil Munawwar Manshur (Sunan Kalijaga State Islamic University Yogyakarta, 2012)
Kasidah Burdah is the work of al-Bu>si>ry, an Arab Egyptian writer, which was created in the 13th century AD. It contains poems of praise to the Prophet. Its birth has made poems of praise to the Prophet grow rapidly in the Arab-Islamic world of literature. This Arabic literary work has a major impact on the development of Sufi literature. This research on Kasidah Burdah uses negative aesthetic theory developed by Hans Robert Jauss. This theory considers that a literary work cannot be separated from the history of its creation and speech. This theory also states that a literary work can only be said to achieve beauty when it is negated. It means that it is able to get out of the initial reality of its reference. The material object of this study is the Arabic text of al-Busīry’s Kasidah Burdah, and its translation in Indonesian. The formal object is the polemic of the interpretation of some verses in Kasidah Burdah concerning the position of the Prophet as a creature, love, maulid of the Prophet, intercession, and tawassul. The method used in this study is defamiliarization method. This method works based on the assumption that readers must change their way of reading a literary work. They cannot read similarly to what the previous readers did. Readers should not be fixated on the previous readings, but they have to produce new meanings which may not be the same as the primary ones.